Phosphate Solubilizing Microorganism and available P on the Rizosphere of some Ages and Distances from the Center of Maize Roots - Niswati, Ainin; Yusnaini, Sri; Arif, Mas Achmad Syamsul (UNIVERSITY OF LAMPUNG, 2008)
Effect of the age and root distance of maize on the population of phosphate solubilizing microorganisms was studied. The rizosphere and non-rhizosphere soil of maize was setup in the special pots with dimension of 60 cm x 60 cm x 30 cm in the glasshouse. The Ultisols soil was planted with maize until the vegetative stages. The results showed that on the distance of > 20 cm from center of roots, the age of maize increase the population of phosphate solubilizing microorganisms. The population of phosphate solubilizing microorganisms in the rhizosphere soil was 8 - 23× more than from those non-rhizosphere soils. On the distance of 0-10 cm, the age of maize affected the number of phosphate solubilizing microorganisms in the rizosphere and non-rhizosphere soil. Available-P (Bray I) was affected by the age and distance of root maize. The highest value was observed on the 7 weeks after planting at a distance of >20 cm. Available P was significantly higher in the rhizosphere soil than that in non-rhizosphere soil, especially at a distance of >20 cm on the 7 weeks after planting. The positive correlation was occurred between phosphate solubilizing microorganism and the value of available-P, soil pH, organic C and total N.